Prevalence of corneal arcus and associated factors in a German population-Results from the Gutenberg Health Study. - Joanna Wasielica-Poslednik; Ulrike Hampel; Lisa Ries; Ruah Faysal; Andreas Schulz; Jürgen H Prochaska; Philipp S Wild; Irene Schmidtmann; Thomas Münzel; Manfred E Beutel; Karl J Lackner; Norbert Pfeiffer; et al. (PLoS ONE)
Purpose We aimed to determine the prevalence of corneal arcus and to identify associated factors in the general population of Germany. Methods The Gutenberg Health Study (GHS) is a population-based cohort study in Germany, which includes an ophthalmological assessment. Refraction, distance-corrected visual acuity, non-contact tonometry and anterior segment imaging were performed for the five-year follow-up examination. Anterior segment photographs were graded for the presence of corneal arcus. Prevalence estimates were computed, and multivariable logistic regression analysis was applied to determine associated factors for corneal arcus including sex, age, spherical equivalent, central corneal thickness, intraocular pressure (IOP), socio-economic status, smoking, BMI, systolic and diastolic arterial blood pressure, HbA1c, HDL-C, LDL-C, triglyceride, and lipid modifying agents. Results A total of 9,850 right and 9,745 left eyes of 9,858 subjects (59.2±10.8 years), 49.0% females were included in this cross-sectional analysis. 21.1% of men (95%-CI: 20.0%- 22.3%) had a corneal arcus in at least one eye, and 16.9% (95%-CI: 15.9%- 18.0%) of women. In multivariable analyses, the presence of corneal arcus was associated with male gender (OR = 0.54 for female, p<0.0001), higher age (OR = 2.54 per decade, p<0.0001), smoking (OR = 1.59, p<0.0001), hyperopia (OR = 1.05 per diopter, p<0.0001), thinner cornea (OR = 0.994 per μm, p<0.0001), higher IOP (OR = 1.02, p = 0.039), higher HDL-C-level (OR = 2.13, p<0.0001), higher LDL-C-level (OR = 1.21, p<0.0001), and intake of lipid modifying agents (OR = 1.26, p = 0.0001). Arcus was not associated with socio-economic status, BMI, arterial blood pressure, and HbA1c. Conclusions Corneal arcus is a frequent alteration of the cornea in Germany and is associated with ocular parameters and systemic parameters of dyslipidemia.